Innovative Modeling and Simulation of Electric Power Systems. Issue 27 (2016) - Neuman, P.
Abstract: In the last decades many papers and textbooks devoted to the computer modeling and analysis of large power system network have been written. For the most part the models and analysis techniques have been developed for large interconnected transmission systems (TS) and synchronous generators. Little, relatively, attention was devoted to the distribution systems (DS) and its major components. As a result, the distribution engineer has not had the same number of tools as the systems engineer to analyze the distribution system under steady-state (power flow) and fault (short circuit) conditions. Without these tools the distribution engineer has been left in the dark (no pun intended) as to the operating characteristics of distribution feeders. Line segments in distribution systems are inherently unsymmetrical. That is, the spacing distances between phases are not equal and the lines are not transposed; as is typically done on high voltage transmission lines. The non-symmetry results in unequal self and mutual impedances. Couple this with line currents that are typically unbalanced and a potential for severe voltage unbalances can occur along with additional line power losses. For a four wire grounded Wye line, the unbalanced operation leads to currents flowing in the neutral and dirt. Original literature uses the term "dirt current". In other literature, the reader will also find the terms "ground" or "earth dirt". This presentation will develop a method for the computation of the "neutral" and "dirt currents" and the power losses that are a result of these currents.